Experimental and numerical analysis of the tensile test using sheet specimens - Cabezas, Eduardo E.; Celentano, Diego J. (Finite elements in analysis and design, 2004)
This paper presents an experimental and numerical study of the mechanical behaviour of SAE 1045 steel sheet specimens during the conventional tensile test. Due to the complex stress state that develops at the neck for high levels of axial deformation, an experimental-numerical methodology is proposed in order to derive the elastic and hardening parameters which characterize the material response. Such methodology is essentially an extension to sheet samples of the well established procedure used for cylindrical ones. The simulation of the deformation process during the whole test is performed with a finite element large strain elastoplasticity-based formulation. Finally, the experimental validation of the obtained numerical results allows to assess the performance of the proposed methodology for the 3D analysis of sheet specimens and, in addition, to discuss the range of applicability of plane stress conditions.